The enterohemorrhagic Escherichia coli effector protein NleF binds mammalian Tmp21 - Olsen, Rachel L.; Echtenkamp, Frank; Cheranova, Dilyara; Deng, Wanyin; Finlay, B. Brett; Hardwidge, Philip R. (My University, 2013)
The human pathogens enterohemorrhagic and enteropathogenic Escherichia coli (EHEC and EPEC), as well as the mouse pathogen Citrobacter rodentium encode type III secretion system (T3SS) effector proteins to promote their survival in the infected host. The mechanisms of action and the host targets of T3SS effectors are under active investigation because of their importance to bacterial virulence. The non-locus of enterocyte effacement (LEE)-encoded protein F, NleF, contributes to E. coli and C. rodentium colonization of piglets and mice, respectively. Here we sought to characterize the host binding partners of NleF. Using a yeast two-hybrid screen, we identified Tmp21, a type-I integral membrane protein and COPI-vesicle receptor involved in trans-Golgi network function, as an NleF-binding partner. We confirmed this interaction using immunoprecipitation and bimolecular fluorescence complementation (BiFC). We expressed a temperature-sensitive vesicular stomatitis virus glycoprotein (tsVSVG) to monitor protein trafficking and determined that NleF slows the intracellular trafficking of tsVSVG from the endoplasmic reticulum to the Golgi.
Keywords: Effector; Enterohemorrhagic E. coli; NleF; Tmp21; Type III secretion